Career Progression of Women: Does Work-life Balance Matter? - Emmanuel Essandoh; Isaac Tetteh Kwao; Doris Akalachiba Asandem; Emmanuel Agyenim Boateng; Barbara Arthur (European Scientific Journal, ESJ, 2023)
The study empirically examined the influence of work-life balance practices on the Career Progression of Women at the Ministry of Gender, Children, and Social Protection (MoGCSP). Given the reliance on an explanatory research design, the study utilized a structured questionnaire for gathering the primary data quantitatively from 209 randomly selected participants. A second-order model was configured in SMART PLS for testing the directional hypotheses formulated. The results indicated that work-life balance practices have a moderately significant positive predictor on both career goal progress and promotion speed. However, it significantly predicts a weak positive variance in professional development ability of career progression. The practical implication is that the Ministry of Gender, Children, and Social Protection through its agency, must continually provide favorable work-life balance practices for its female staff to make female workers happy, satisfied, and progress in their various careers. The study offers a better theoretical understanding of how work-life balance, if handled well, may influence female workers' career progression, even in a situation where men predominate, as per role theory. Empirically, the study enriches the theoretical understanding of how work-life balance, if properly managed, would affect female workers in progression in their careers even in a masculine context, as established by the role theory in Sub-Saharan country-context.